Understanding and responding to challenges students face when engaging in carbon cycle pool-and-flux reasoning. Issue 2 (9th November 2020) - Covitt, Beth A.; Parker, Joyce M.; Kohn, Craig; Lee, May; Lin, Qinyun; Anderson, Charles W.
Abstract: Carbon cycle pool-and-flux reasoning is a critical facet of climate literacy. This article begins with discussion of why this type of reasoning is both challenging and important. Results from two studies are reported. The first describes students' approaches to carbon cycle pool-and-flux reasoning. The second describes and reports results from an instructional intervention designed to scaffold secondary students' model-based pool-and-flux reasoning. Before instruction, most secondary students employed informal reasoning approaches including good versus bad and correlation heuristics to carbon cycle pool-and-flux problems. After instruction, the portion of students employing goal model-based pool-and-flux reasoning increased from 27 to 52 percent. This study builds on previous and current research to offer a promising instructional approach to scaffolding improvements in students' model-based pool-and-flux reasoning. Supplemental data for this article is available online at https://doi.org/10.1080/00958964.2020.1847882 .